Simulation of Electronic Structure of Gallium Phosphide Nanocrystals Using Ab Initio Density Functional Theory/3-21 (Journal of the College of Basic Education, 2022)
Ab initio (Ab –initio is the Latin term for "from first principles", or "from scratch this name is given to computations which are derived directly from theoretical principles, with no inclusion of experimental data.) restricted Hartree-Fock method coupled based methods as well as Density functional theory is used to determine the electronic structure and physical properties of Gallium phosphide (GaP) nanocrystals with used diamondoids structure begin Diamantane, Tetramantane and Hexamantane with different sizes are investigated. Investigated properties include cohesive energy, dihedral angle, bond length, tetrahedral angle, and degeneracy of energy levels. Results revealed that electronic properties converge to some limit as the size of the Gallium phosphide material in several properties. Increasing nanocrystals size also resulted in a decrease in cohesive energy (absolute value) decreased with increased NO. of atoms, the dihedral angle and tetrahedral are nearest of the ideal value. Bond length was very close of the experiment value